High Bone Mass–Causing Mutant LRP5 Receptors Are Resistant to Endogenous Inhibitors In Vivo. (22nd September 2015) - Niziolek, Paul J; MacDonald, Bryan T; Kedlaya, Rajendra; Zhang, Minjie; Bellido, Teresita; He, Xi; Warman, Matthew L; Robling, Alexander G
Abstract: Certain missense mutations affecting LRP5 cause high bone mass (HBM) in humans. Based on in vitro evidence, HBM LRP5 receptors are thought to exert their effects by providing resistance to binding/inhibition of secreted LRP5 inhibitors such as sclerostin (SOST) and Dickkopf homolog‐1 (DKK1). We previously reported the creation of two Lrp5 HBM knock‐in mouse models, in which the human p.A214V or p.G171V missense mutations were knocked into the endogenous Lrp5 locus. To determine whether HBM knock‐in mice are resistant to SOST‐ or DKK1‐induced osteopenia, we bred Lrp5 HBM mice with transgenic mice that overexpress human SOST in osteocytes ( 8kb Dmp1 ‐ SOST ) or mouse DKK1 in osteoblasts and osteocytes ( 2.3kb Col1a1 ‐ Dkk1 ). We observed that the 8kb Dmp1 ‐ SOST transgene significantly lowered whole‐body bone mineral density (BMD), bone mineral content (BMC), femoral and vertebral trabecular bone volume fraction (BV/TV), and periosteal bone‐formation rate (BFR) in wild‐type mice but not in mice with Lrp5 p.G171V and p.A214V alleles. The 2.3kb Col1a1‐Dkk1 transgene significantly lowered whole‐body BMD, BMC, and vertebral BV/TV in wild‐type mice and affected p.A214V mice more than p.G171V mice. These in vivo data support in vitro studies regarding the mechanism of HBM‐causing mutations, and imply that HBM LRP5 receptors differ in their relative sensitivity to inhibition by SOST and DKK1. © 2015 American Society for Bone and Mineral Research.